2021
DOI: 10.3390/pharmaceutics13091421
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Punctal Plugs for Controlled Ocular Drug Delivery

Abstract: Dry eye disease is a common ocular disorder that is characterised by tear deficiency or excessive tear evaporation. Current treatment involves the use of eye drops; however, therapeutic efficacy is limited because of poor ocular bioavailability of topically applied formulations. In this study, digital light processing (DLP) 3D printing was employed to develop dexamethasone-loaded punctal plugs. Punctal plugs with different drug loadings were fabricated using polyethylene glycol diacrylate (PEGDA) and polyethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 89 publications
0
27
0
Order By: Relevance
“…One consideration was the volume of the rig. The volume used was much higher than previous studies ( Angkawinitwong et al, 2017 ; Xu et al, 2021 ); 2.2 mL vs 200 μL, respectively. However, these models are too small for the contact lenses to fit and retain their shape as they were predominantly designed for subconjunctival formulations.…”
Section: Resultsmentioning
confidence: 81%
“…One consideration was the volume of the rig. The volume used was much higher than previous studies ( Angkawinitwong et al, 2017 ; Xu et al, 2021 ); 2.2 mL vs 200 μL, respectively. However, these models are too small for the contact lenses to fit and retain their shape as they were predominantly designed for subconjunctival formulations.…”
Section: Resultsmentioning
confidence: 81%
“…The results revealed that the drug was released for up to 7 days from the punctual plug developed with 20% w/w PEG 400 and 80% w/w PEGDA, whereas the drug was released over 21 days from the punctual plug comprising 100% PEGDA. This research demonstrates the efficiency of DLP in developing various extended release personalized ocular devices ( Xu et al, 2021b ). Further, Rodríguez-Pombo et al (2022) , introduced a novel volumetric 3D printing technology, which is an advancement and is superior to DLP, intended to rapidly fabricate medicines.…”
Section: A Glimpse Of Various 3d Printing Technologiesmentioning
confidence: 68%
“…Lastly, in an innovative and intriguing work by Xu et al (2021b) , a smartphone was used in fabricating personalized 3D printed tablets (warfarin sodium printlets). In this technology, the light emitted from the smartphone's screen was used to photopolymerize the liquid resin to obtain a solid structure.…”
Section: A Glimpse Of Various 3d Printing Technologiesmentioning
confidence: 99%
“…3D printing is a key manufacturing method for customisable devices (Awad et al, 2020;Elbadawi et al, 2020;Vivero-Lopez et al, 2021;Xu et al, 2021c;Xu et al, 2020). Among different categories of 3D printing technologies, vat photopolymerisation-based 3D printing is a type of technique that creates physical objects from a vat of liquid resins under light irradiation in a layerby-layer fashion, offering superior resolution and a smooth surface finish that other 3D printing technologies cannot compete with (Ng et al, 2020;Xu et al, 2021a;Xu et al, 2021b). In this study, we develop, manufacture, and validate a 3D printed biocatalytic device (termed Printzyme) for the removal of drugs from wastewater at concentrated point sources such as hospitals or pharmaceuticals facilities.…”
Section: Introductionmentioning
confidence: 99%